Efficacy of rituximab in slowing down progression of rheumatoid arthritis–related interstitial lung disease: data from the NEREA Registry. (28th January 2020) - Vadillo, Cristina; Nieto, Maria Asuncion; Romero-Bueno, Fredeswinda; Leon, Leticia; Sanchez-Pernaute, Olga; Rodriguez-Nieto, Maria Jesus; Freites, Dalifer; Jover, Juan Angel; Álvarez-Sala, Jose Luis; Abasolo, Lydia
Abstract: Objectives: To asses the clinical course in RA-related interstitial lung disease (RA-ILD) patients with and without rituximab (RTX). The influence of other variables was also evaluated. Methods: A longitudinal multicentre study was conducted in RA diagnosed with ILD from 2007 until 2018 in Madrid. Patients were included in a registry [pNEumology RhEumatology Autoinmune diseases (NEREA)] from the time of ILD diagnosis. The main endpoint was functional respiratory impairment (FI), when there was a decline ≥5% in the predicted forced vital capacity compared with the previous one. Pulmonary function was measured at baseline and in follow-up visits every 6–12 months. The independent variable was therapy with RTX. Covariables included sociodemographic, clinical, radiological and other therapies. Survival techniques were used to estimate the incidence rate (IR) and 95% CI of functional impairment, expressed per 100 patient-semesters. Cox multivariate regression models were run to examine the influence of RTX and other covariates on FI. Results were expressed as the hazard ratio (HR) and CI. Results: A total of 68 patients were included. FI occurred in 42 patients [IR 23.5 (95% CI 19, 29.1)] and 50% of them had FI within 1.75 years of an ILD diagnosis. A multivariate analysis showed that RTX exposure resulted in a lower risk of FI compared with non-exposure [HR 0.51 (95% CI 0.31, 0.85)]. Interstitial pneumonia, glucocorticoids, disease activity and duration also influenced FI. Conclusion: RA-ILD patients deteriorate over time, with the median time free of impairment being <2 years. Patients exposed to RTX had a higher probability of remaining free of FI compared with other therapies. Other factors have also been identified.